Answer:
X ≤ 5/3
y ≥ -1/3
Explanation:
in the first inequality
x-y≤ 2
X ≤ 2+y equation 1
for the second inequality
x + 2y ≥ 1
X ≥ 1-2y. .... equation 2
we now need to substitute the value of x in equation 1 in equation 2
2+y ≥ 1 -2y
1 ≥ -3y
-1/3 ≤ y
but X ≤ 2+y
X ≤ 2+-1/3
x≤2+y
replace the x with 2+y in the next equation
2+y +2y≥1
solve the equation simultaneously:
2+3y≥1
3y≥1-2
3y≥-1
y≥-1/3
Since you found y, replace it in the first equation to find the value of x
x-(-1/3)≤2
x+1/3≤2
x≤2-1/3
x≤5/3
5.3m questions
6.9m answers